Nonlocality-Enabled Magnetic Free Optical Isolation in Hyperbolic Metamaterials - Janaszek, Bartosz (Materials (Basel), 2021)
Hereby, we present an optical isolator (optical diode) based on a hyperbolic metamaterial (HMM). We demonstrate that a grating-free planar linear non-magnetic HMM structure deposited on a high-index substrate, which, due to presence of strong spatial dispersion (non-locality), reveals asymmetrical transmittance and reflectance characteristics for light of arbitrary polarization within a wide angular and spectral range. The presented device may be efficiently utilized to completely block backward and enforce unidirectional propagation in free space and integrated systems without the use of magnetooptical or non-linear effects.